2008
DOI: 10.1111/j.1365-246x.2008.03800.x
|View full text |Cite
|
Sign up to set email alerts
|

Simulating three-dimensional seismograms in 2.5-dimensional structures by combining two-dimensional finite difference modelling and ray tracing

Abstract: S U M M A R YFinite difference (FD) simulation of elastic wave propagation is an important tool in geophysical research. As large-scale 3-D simulations are only feasible on supercomputers or clusters, and even then the simulations are limited to long periods compared to the model size, 2-D FD simulations are widespread. Whereas in generally 3-D heterogeneous structures it is not possible to infer the correct amplitude and waveform from 2-D simulations, in 2.5-D heterogeneous structures some inferences are poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…However, note that on one seismogram, p = p(t) is different for the various seismic phases. Miksat et al (2008) showed that using ray tracing to calculate the F factor for each phase, line source seismogram can be corrected to obtain the point source seismogram, phase by phase. However, ray tracing is complicated and processing phase by phase is cumbersome.…”
Section: -D Spreadingmentioning
confidence: 99%
“…However, note that on one seismogram, p = p(t) is different for the various seismic phases. Miksat et al (2008) showed that using ray tracing to calculate the F factor for each phase, line source seismogram can be corrected to obtain the point source seismogram, phase by phase. However, ray tracing is complicated and processing phase by phase is cumbersome.…”
Section: -D Spreadingmentioning
confidence: 99%
“…All spatial and temporal modelling parameters are listed in Table 1. The source is implemented by adding the stress glut (Olsen et al 2006; Miksat et al 2008) to the source gridpoint. The source time function of the added stresses for the considered M L = 3.8 earthquake is described by a Herrman window with a half width of 0.5 s. The moment magnitude, which is needed to calculate the stress glut, is obtained from local magnitude by the empirical relationship of Lin & Lee (2008) for earthquakes in Taiwan.…”
Section: Numerical Modellingmentioning
confidence: 99%
“…where ω is the angular frequency, the quantity σ is defined as σ=cr, c is the acoustic wave speed, and r is the distance. However, the asymptotic filter transfer function is derived from a half‐space, which is an approximation to our case, such an approximation has been applied to the inhomogeneous media with acceptable results (Miksat, Müller and Wenzel ; Auer et al . ).…”
Section: Sichuan Data Applicationsmentioning
confidence: 99%